Cracking geriatric complexity: key messages from the Italian Society of Geriatrics Hospital and Territory Young Masterclass - Liliana Mazza; Francesca Crosta; Roberto Caragnulo; Moira Ceci; Claudio De Lucia; Simone Dini; Lorenzo Palleschi (Geriatric Care, 2025)
The population is aging worldwide, and multimorbidity, polypharmacy, atypical symptoms, and geriatric syndromes are highly prevalent in older adults. Therefore, a personalized approach to care is essential. Adequate training for geriatricians is mandatory to guarantee homogeneity of care for complex patients. The Italian Society of Geriatrics Hospital and Territory (Società Italiana Geriatria Ospedale e Territorio, SIGOT) is committed to providing appropriate geriatric education through various projects and initiatives. Notably, the masterclass “Taking charge of the complexity between different care settings”, which was held in Bertinoro (Emilia-Romagna, Italy), addressed key geriatric topics in geriatrics such as antimicrobial stewardship, malnutrition, sarcopenia, psychogeriatrics, cardiogeriatrics, and transitional care. The event brought together young specialists and residents with experienced experts for 3 days of intensive learning, knowledge sharing, and professional networking. This consensus statement article summarizes the most important concepts discussed during this impactful event.